Neurotensin receptors in pancreatic ductal carcinomas - Körner, Meike; Strobel, Oliver; Büchler, Markus W. (EJNMMI Research, 2015)
The frequent expression of neurotensin receptors (NT-R) in primaries of pancreatic ductal carcinomas has triggered the development of radioactive neurotensin analogs for possible in vivo targeting of these tumors. However, the complete lack of information regarding NT-R in liver metastases of pancreatic cancer and pancreatic intraepithelial neoplasia (PanIN) makes an in vitro study of NT-R in these tissues indispensable.
Gesehen am 22.08.2017